PERAN SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG KAKI LIMA DIKOTA DENPASAR TAHUN 2014 - Loebaloe, Aldi Juliant; Pascarani, Ni Nyoman Dewi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACT Street vendors are jobs in informal sector whose presence become pros and cons in every city especially Denpasar. Street vendors sell their merchandise around public facilities which ultimately disturb public order. Civil Service Police Unit is one of the apparatures of the local government which have an important role in conducting the control of street vendors in the city of Denpasar. The study was to look at the role of the Civil Service Police Unit in controlling street vendors in the city of Denpasar and the obstacles they had. This study used a qualitative method and theory employed was performance measurement proposed by Agus Dwiyanto with the indicators used were productivity, quality of service, responsiveness, responsibility and accountability. To obtain the data, the researcher conducted observations to see firsthand the phenomenon that occur in the field and conduct in-depth interviews with informants related to the Civil Service Police Unit of Denpasar. The results of this study show that the role of the Civil Service Police Unit of Denpasar in controlling the vendors was not optimal this is because the productivity of the Civil Service Police Unit was not optimal due to the lack of human resources and facilities and infrastructure. Quality of Service of the Civil Service Police was not maximal for most of the personnel of the police only have high school educational background in as well as the quality of facilities and infrastructure was poor. The responsiveness of municipal police was not optimal because the police unit had not been able to meet the needs of vendors i.e. a land to sell in. In addition, sanctions and punishment had not been empowered in accordance with the local government regulation in the city of Denpasar so that the responsibility of the Civil Service Police is not optimal. The barriers faced by the Civil Service Police are internal and external obstacles. The internal barriers are the lack of human resources from the civil service police themselves as well as the ability of the personnel is still lacking, while the external barriers are that there are rogues that back up the street vendors, a lack of awareness of vendors to comply with the regulations and the lack of land for street vendors themselves to sell in. Therefore the suggestion of the researcher is that the Civil Service Police need to increase the number of members / personnel as well as paying more attention to facilities and infrastructure to be used. In addition, there is a need to quickly draft legislation concerning the zones that can be used by street vendors to sell in and they must be stricter in giving punishment or sanctions for those who violate the rules. Keywords: Role, Civil Service Police Unit, Street Vendors